1989
DOI: 10.1111/j.1471-4159.1989.tb11798.x
|View full text |Cite
|
Sign up to set email alerts
|

Monoclonal Antibody to Embryonic CNS Antigen A2B5 Provides Evidence for the Involvement of Membrane Components at Sites of Alzheimer Degeneration and Detects Sulfatides as Well as Gangliosides

Abstract: Immunohistological and biochemical studies were initiated to determine whether or not neural membrane components were associated with degenerative changes characteristic of Alzheimer's disease (AD). Monoclonal antibody A2B5, developed against embryonic chick retinal cells and previously shown to react with neural surface gangliosides, was applied to formalin-fixed sections of control and AD brain tissue. Frontal cortex and hippocampus of AD cases exhibited high levels of A2B5 immunoreactivity within those neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

1991
1991
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(30 citation statements)
references
References 36 publications
1
29
0
Order By: Relevance
“…In AD, many neurofibrillary tangles, neuropil threads, and dystrophic neurites react strongly with A2B5 (36). Although the amount of gangliosides and their patterns are similar in control and in AD cases (37), an observation was made that the A2B5 antibody reacted with human brain c-series gangliosides and, unexpectedly, sulfatides (38). The brain gangliosides of different transgenic mouse models of AD have been analyzed and compared with those of age-matched wild-type mice (39)(40)(41)(42).…”
Section: Ganglioside Metabolism In Admentioning
confidence: 99%
“…In AD, many neurofibrillary tangles, neuropil threads, and dystrophic neurites react strongly with A2B5 (36). Although the amount of gangliosides and their patterns are similar in control and in AD cases (37), an observation was made that the A2B5 antibody reacted with human brain c-series gangliosides and, unexpectedly, sulfatides (38). The brain gangliosides of different transgenic mouse models of AD have been analyzed and compared with those of age-matched wild-type mice (39)(40)(41)(42).…”
Section: Ganglioside Metabolism In Admentioning
confidence: 99%
“…Both antigens were down-regulated as the cells differentiated to oligodendrocytes, making them likely candidates to be the A2B5 antigens used routinely as cell surface markers for O2A progenitors. Others have demonstrated A2B5-reactive gangliosides by TLC overlay in neural tissue that do not correspond in chromatographic mobility to any of the major brain gangliosides (Fredman et al, 1984;Majocha et al, 1989). Similarly, the antigens in oligodendrocyte progenitors were present in relatively low amounts that were undetectable with orcinol staining.…”
Section: Discussionmentioning
confidence: 92%
“…MAb A2B5 recognizes not only GQlc and GT3 (20J4.35) but also 9-0-acetyl GT3. disialogangliosides such as GQlb, and sulfatides (34)(35)(36), and these authors did not confirm whether or not the AZB5-binding molecules in the glioma cells corresponded to C-series polysialogangliosides. Dubois et al (19) reported the presence of GT3 in five of seven human melanoma cell lines by TLC immunostaining with MAb 18B8 directed against GT3, but they did not examine human glioma cells.…”
Section: Discussionmentioning
confidence: 96%